2008
DOI: 10.1016/j.biochi.2008.02.011
|View full text |Cite|
|
Sign up to set email alerts
|

DNA triple helices: Biological consequences and therapeutic potential

Abstract: DNA structure is a critical element in determining its function. The DNA molecule is capable of adopting a variety of non-canonical structures, including three-stranded (i.e. triplex) structures, which will be the focus of this review. The ability to selectively modulate the activity of genes is a longstanding goal in molecular medicine. DNA triplex structures, either intermolecular triplexes formed by binding of an exogenously applied oligonucleotide to a target duplex sequence, or naturally occurring intramo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
199
0
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 262 publications
(218 citation statements)
references
References 160 publications
2
199
0
2
Order By: Relevance
“…It can be envisioned that discrete substates within the native state ensemble play important roles in the biology of other non-B-DNA secondary structures, such as G-quadruplexes (55-57), iDNAs (58-61), cruciforms (62)(63)(64), and triple helical H-DNA like structures (65)(66)(67)(68)(69)(70), inter alia (41,67,(71)(72)(73)(74)(75)(76). Given the diverse range of secondary structural elements and highly folded 3 dimensional structures common to many biologically important macromolecules, the realization of rough energy landscapes and discrete microstates for nucleic acids should prove important for understanding the broad range of mechanisms that modulate nucleic acid biology.…”
Section: Resultsmentioning
confidence: 99%
“…It can be envisioned that discrete substates within the native state ensemble play important roles in the biology of other non-B-DNA secondary structures, such as G-quadruplexes (55-57), iDNAs (58-61), cruciforms (62)(63)(64), and triple helical H-DNA like structures (65)(66)(67)(68)(69)(70), inter alia (41,67,(71)(72)(73)(74)(75)(76). Given the diverse range of secondary structural elements and highly folded 3 dimensional structures common to many biologically important macromolecules, the realization of rough energy landscapes and discrete microstates for nucleic acids should prove important for understanding the broad range of mechanisms that modulate nucleic acid biology.…”
Section: Resultsmentioning
confidence: 99%
“…Both GG II and AA II pairs have been observed in triplex structures formed by DNA and a third strand of oligonucleotide (DNA or RNA), where groups -NH 2 of both Guanines are occupied in the formation of hydrogen bonds and the O6 of Guanine and N7 of Adenine are located towards the minor and major groove respectively 24,25 , allowing the inclusion of divalent metal ions 3 . The inclusion of antiviral drugs and antibiotics is produced in areas of DNA with high concentrations of AT base pair, where the -NH 2 group is absent; in fact neomycin stabilizes DNA triplex structure with TAT bases triples 3,5,25 .…”
Section: Resultsmentioning
confidence: 99%
“…Although GG pair does not participate directly in that kind of recognition, it has been suggested that N7 and O6 atoms of the GG and GA pairs form polar hydrogen bonds with aminoglycoside antibiotics 2,[20][21][22] . These drugs are also inserted in DNA triplex structures 23,24 , where N7 and O6 atoms are found available in the purine bases of the third strand oligonucleotide 25 . In these complex structures, most likely associated with DNA repairing processes, it also observed that the Hoogsteen sides of the DNA nitrogen bases form hydrogen bonds with the WC sides of the third strand of DNA, forming the GG and AA pairs 23,24 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In antigene technology, a single-stranded homopyrimidine triplex-forming oligonucleotide (TFO) added from outside may bind with homopurinehomopyrimidine stretch in target duplex DNA by Hoogsteen hydrogen bonding to form pyrimidine motif triplex, where T•A:T and C + •G:C base triplets are formed [3,4]. The formed triplex inhibits RNA polymerase and transcription factors-mediated transcription of target gene due to its steric hindrance, which may result in downregulation of expression level of target gene [3,4].…”
Section: Introductionmentioning
confidence: 99%